The effect of origin and genetic processes of low molecular weight aromatic hydrocarbons in petroleum on their stable carbon isotopic compositions - Le Metayer, Pierre; Grice, Kliti; Chow, C.; Caccetta, Louis; Maslen, Ercin; Dawson, Daniel; Fusetti, L. (Pergamon, 2014)
Stable carbon isotopic compositions of individual low molecular weight aromatic hydrocarbons, such as alkylbenzenes, alkylnaphthalenes and alkylphenanthrenes, were measured from a set of oils, mostly from the North-West shelf of Australia, of varying age, facies type and thermal maturity. The objective was to assess the influence of thermal maturity and source during generation of these aromatics on their stable carbon isotopic compositions. For most of the oils studied, δ13C of the aromatic components show a 13C depletion as the degree of methylation increases. For the alkylnaphthalenes, the 13C depletion is most pronounced for low maturity oils compared to high maturity oils. δ13C of the methyl groups of these alkylnaphthalenes were calculated and the resulting data display significant differences between ‘mature’ and ‘immature’ oils, suggesting that isotopically lighter methyl groups are ‘released’ as thermal maturation proceeds. Therefore, we propose an isotopic fractionation associated with the methyl transfer mechanisms affecting low molecular weight aromatic hydrocarbons during diagenesis.